2016
DOI: 10.1016/j.icarus.2016.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally induced surface slope-instabilities and the activation of CO2 activity on comet 103P/Hartley 2

Abstract: Comet 103P/Hartley 2 has diurnally controlled, CO 2 -driven activity on the tip of the small lobe of its bilobate nucleus. Such activity is unique among the comet nuclei visited by spacecraft, and suggests that CO 2 ice is very near the surface, which is inconsistent with our expectations of an object that thermophysically evolved for ~45 million years prior to entering the Jupiter Family of comets. Here we explain this pattern of activity by showing that a very plausible recent episode of rapid rotation (rota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Transient events associated to such collapse have also been observed on 67P Grün et al, 2016;Pajola et al, 2017). Other comets show similar link between activity and morphology , and also with landslides in areas covered with fine dust like on comet 103P (Steckloff et al, 2016).…”
Section: Active Sourcesmentioning
confidence: 66%
See 1 more Smart Citation
“…Transient events associated to such collapse have also been observed on 67P Grün et al, 2016;Pajola et al, 2017). Other comets show similar link between activity and morphology , and also with landslides in areas covered with fine dust like on comet 103P (Steckloff et al, 2016).…”
Section: Active Sourcesmentioning
confidence: 66%
“…the sudden release of a large quantity of gas and dust, driven by mechanisms that are still debated. While outbursts have usually been interpreted as akin to an explosive decompression, this interpretation is challenged by EPOXI and Rosetta data and the associated models which suggest that the transient release of material can be well explained by avalanches (Steckloff et al, 2016) or topographic collapses (pits, cliffs, Vincent et al (2016)). Spacecraft observations have shown that such events are more likely to occur around perihelion and in the outbound orbit, but not always.…”
Section: Temporalitymentioning
confidence: 99%
“…The formation of these new synapses, and the loss of some old ones, mean that spicule movement comes under the is now causing the strong torque. A similar sequence of events could have occurred in comet 103P/Hartley 2, which was visited by the Deep Impact Extended Investigation (DIXI) space mission 8,10 in 2010.…”
Section: S C O T T W E M M O N Smentioning
confidence: 69%
“…If a comet is spun up to a rotation rate at which the centrifugal force near the equator surpasses gravitational and cohesive forces, landslides and partial or even catastrophic fragmentation can occur [6][7][8] . Such events would be accompanied by strong sublimation (transformation of ice into gas) and dust production from newly exposed areas, which is one possible cause of sudden increases in brightness called outbursts.…”
mentioning
confidence: 99%
“…On 67P, multiple landslide deposits are identified in close association with cliffs. These observations suggest that cliff collapse is an important process in reshaping cometary surfaces (Britt et al, ; Pajola et al, ; Steckloff et al, ; Steckloff & Samarasinha, ). OSIRIS observations show a direct evidence of the occurrence of a cometary landslide, with the resulting production of a newly formed boulder talus located at the base of the scarp (see the Aswan case; Pajola et al, ).…”
Section: Data Set: Identification Of Landslides On Comet 67pmentioning
confidence: 99%